Między "Cyrulikiem sewilskim" a "Pierścieniem Nibelunga". Przyczynek do muzycznej refleksji o pieniądzu i ekonomii twórczości - Siechowicz, Paweł (Res Facta Nova, 2021)
The article is an invitation to reflect on the theme of money and the role of economic incentives in the creative act. Pointing to the abundant presence of the theme of money in opera plots, the author proposes to study the economics of creativity of particular composers taking account of the various valuations of money expressed in their works. The ground for such reflection is set forth by the comparison of two operas that express two extreme views on money and its role for creativity: Gioacchino Rossini’s The Barber of Seville and Richard Wagner’s The Ring of the Nibelung. Comparing different ways in which Figaro and Alberich approach money provides a starting point for the comparison of two creative acts that can be found in the two works: Figaro’s invention of a creative solution for Almaviva’s problem (affirmation of money) and Siegfried’s forging of a sword accompanied by Mime’s efforts to make a sleeping potion (rejection of money). The analysis of the musical form of the two scenes, however, shows the indebtedness of Wagner to Rossini. Although Wagner openly rejects the musical principles of his Italian predecessor, the dramaturgy of his music is based on the dramaturgical formulas developed in Italian operas. The two approaches towards money can be linked to the opposing views of Adam Smith and Karl Marx regarded as fathers of the classical and Marxian schools of political economy. Thus, the two operas can be seen as border posts of the territory in which music and economy intersect.